2010
DOI: 10.1007/s12206-010-0611-1
|View full text |Cite
|
Sign up to set email alerts
|

Condensation heat transfer coefficients of HFC245fa on a horizontal plain tube

Abstract: In this study, condensation heat transfer coefficients (HTCs) of HCFC22, HCFC123, HFC134a and HFC245fa are measured on a horizontal plain tube 19.0 mm outside diameter. All data are taken at the vapor temperature of 39 with a wall subcooling temperature 3-8 . Test results show the HTCs of newly developed alternative low vapor pressure refrigerant, HFC245fa, on a smooth tube are 9.5% higher than those of HCFC123 while they are 3.3% and 5.6% lower than those of HFC134a and HCFC22 respectively. Nusselt's predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…R245fa (1,1,1,3,3-pentafluoropropane) is a hydrofluorocarbon that is under consideration for use as a working fluid in organic Rankine cycles with low-temperature heat sources. It also is of interest for use as a blowing agent and in centrifugal chillers . It is important to have accurate models for the thermophysical properties of working fluids to efficiently design equipment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…R245fa (1,1,1,3,3-pentafluoropropane) is a hydrofluorocarbon that is under consideration for use as a working fluid in organic Rankine cycles with low-temperature heat sources. It also is of interest for use as a blowing agent and in centrifugal chillers . It is important to have accurate models for the thermophysical properties of working fluids to efficiently design equipment.…”
Section: Introductionmentioning
confidence: 99%
“…1−4 It also is of interest for use as a blowing agent 5 and in centrifugal chillers. 6 It is important to have accurate models for the thermophysical properties of working fluids to efficiently design equipment. Recently, a new equation of state has been developed by Akasaka et al 7 that provides thermodynamic properties for R245fa.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For example, R245fa and R236fa are excellent blowing agents to replace hydrochlorofluorocarbons for its desirable characteristics and could be used as working fluids in high-temperature heat pumps and power cycles . R245fa is also used as one component of refrigerant mixtures in centrifugal chillers for its environmental safety and high thermodynamic efficiency . In addition, these compounds may be suitable as cleaning solvents, release agents, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that optimum fin spacing should be between 0.2 mm and 0.5 mm depending upon its fin height and fin thickness. Park et al [2] reported a comprehensive study of condensation heat transfer coefficients on horizontal plain tube using a wide range of available different refrigerants. Kumar et al [3] investigated the condensation heat transfer for steam and refrigerant R-134a on two different types of finned tubes as circular integral-fin tubes (CIFTs) and spine integral-fin tubes (SIFTs).…”
Section: Introductionmentioning
confidence: 99%